Documenting Abundance and Use of Underutilized Plant Species in the Mid Hill Region of Nepal - Khanal, Rajib; Timilsina, Arbindra; Pokhrel, P; Yadav, Ram Kailash P (Ecoprint: An International Journal of Ecology, 2015)
Around the world, many communities depend on plant species that are outside the mainstream of agricultural research and development. These species are also known by various names, such as ‘underutilized crops’ ‘neglected crops, poor people’s crops’ or ‘third order crops’. More recently, they have been designated as crop for the future agriculture. Changing human perception and custodian, changing food habits, influence of globalization are the major factors leading to low priority to the local crop products. The study of underutilized plant species of the mid hill region is an attempt to highlight the food, fruits, vegetables, pulses and medicinal plants; and their mode of use by the local people. The study was conducted in two VDCs; Siddeshwor of Palpa and Hastichaur of Gulmi districts. A total of 52 plant species belonging to 27 families were recorded to be used frequently by the people of Siddeshwor and Hastichaur VDCs. Declining consumption of these local crop varieties at local level and low demand in the local market due to eroding traditional knowledge are main reasons for the farmers being unwilling to grow these crops. ECOPRINT 21: 63-71, 2014 DOI: http://dx.doi.org/10.3126/eco.v21i0.11906